H3 ubiquitination by NEDD4 regulates H3 acetylation and tumorigenesis - Zhang, Xian (Nat Commun, 2017)
Dynamic changes in histone modifications under various physiological cues play important roles in gene transcription and cancer. Identification of new histone marks critical for cancer development is of particular importance. Here we show that, in a glucose-dependent manner, E3 ubiquitin ligase NEDD4 ubiquitinates histone H3 on lysine 23/36/37 residues, which specifically recruits histone acetyltransferase GCN5 for subsequent H3 acetylation. Genome-wide analysis of chromatin immunoprecipitation followed by sequencing reveals that NEDD4 regulates glucose-induced H3 K9 acetylation at transcription starting site and enhancer regions. Integrative analysis of ChIP-seq and microarray data sets also reveals a consistent role of NEDD4 in transcription activation and H3 K9 acetylation in response to glucose. Functionally, we show that NEDD4-mediated H3 ubiquitination, by transcriptionally activating IL1α, IL1β and GCLM, is important for tumour sphere formation. Together, our study reveals the mechanism for glucose-induced transcriptome reprograming and epigenetic regulation in cancer by inducing NEDD4-dependent H3 ubiquitination.